INCREASING THE SUCCESS OF WOMEN'S MSMES AMID COVID-19 BASED ON SOCIO-ECONOMIC PERSPECTIVES THROUGH CONTEXTUAL VARIABLES - Novie Noordiana R Y; Khanifatul Khusna (Universitas Lancang Kuning, 2022)
One of the roles of MSMEs in supporting the Indonesian economy is reducing poverty through providing employment. Based on market research by USAID and IFC explaining that women's participation in the business sector is increasing. This research aims to explore determination in the form of contextual variabel to influencing the success of women's MSMEs during the COVID 19 pandemic, and their impact on the socioeconomic. This research uses quantitative methods. Data was taken from 400 respondents in 8 sub-districts in Surabaya, then processed using the SPSS program. Data collection instruments used questionnaire. Regression test results obtained an observation F value of 379,195 while the F table on F (8/405: 0.05) is 2.04. Means the number F is greater than F table, where simultaneously the independent variables consist of: Access to capital, Government Support, Innovation, Excellence and Competitive Position, Consumer Orientation, Business Plan, Marketing Communication, and Women's power have a significant influence on the success of women's MSMEs. While the results of the t test show that partially Innovation with an observation value of t is 2.546, Business Plan with an observation value of t is 4.727, and finally the Advantages of Women with an observation value of t is 8.768 affect the success of women-owned MSMEs during the Covid 19 pandemic. Economic condition of the women-owned MSMEs during the pandemic Covid 19 tends to be stable while the social conditions are declining